Memperluas Inovasi Olahan Umbi-umbian dan Meningkatkan Masyarakat Sadar Stunting di Desa Siahap, Kecamatan Bintang Bayu - Aulia Syahrani Hafiza; Dede Prasetia; Riski Maulana; Rizka Hanum Mendrofa; Widya Anggi Ramadhana (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study aims to provide innovation from local food processing made from tubers. Where most of the livelihoods of the Siahap village community are farming. One of the most dominating is the cultivation of Cassava or often known as Cassava. Cassava itself is a commodity that is chosen by the people of Siahap village. Besides being easy to cultivate, cassava can also be processed into various needs and processed foods. Cassava also has a lot of protein and fiber which is good for health. In addition, cassava can also be a food that can increase nutritional intake for pregnant women in preventing stunting. The high number of stunting cases has resulted in Indonesia being included in the top five countries with the highest stunting cases in the world. The main prevention of stunting is to pay attention to the nutrition of pregnant women by consuming foods that can fulfill nutrition for both mother and child. Besides generally discussing the benefits of tubers, this article also contains innovations in the form of increasing the Micro Business Activity Unit in Siahap village by processing cassava.